2004
DOI: 10.12806/v3/i3/ab3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Service Learning for Future Leaders of Youth Organizations

Abstract: In this application brief I share a case study assignment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…First, an increase in altruistic calling and emotional healing is not very surprising and echoes previous research showing that service-learning participation has led to an increase in civic engagement knowledge and awareness of societal issues (Melchior and Bailis 2002), respectful attitudes and caring towards diverse groups (Hoover and Webster 2004;Terry and Bohnenberger 2003;Yates and Youniss 1996), civic engagement and political efficacy (Billig 2000;Billig, Root, and Jesse 2005;Hildreth 2000), sense of civic efficacy (Kahne and Westheimer 2006;Morgan and Streb 2001) and longitudinal civic participation (Youniss, McLellan, and Yates 1997). …”
Section: Discussionsupporting
confidence: 64%
“…First, an increase in altruistic calling and emotional healing is not very surprising and echoes previous research showing that service-learning participation has led to an increase in civic engagement knowledge and awareness of societal issues (Melchior and Bailis 2002), respectful attitudes and caring towards diverse groups (Hoover and Webster 2004;Terry and Bohnenberger 2003;Yates and Youniss 1996), civic engagement and political efficacy (Billig 2000;Billig, Root, and Jesse 2005;Hildreth 2000), sense of civic efficacy (Kahne and Westheimer 2006;Morgan and Streb 2001) and longitudinal civic participation (Youniss, McLellan, and Yates 1997). …”
Section: Discussionsupporting
confidence: 64%
“…It is likely the case that students participated in community service or service learning in a wide variety of classes in many disciplines; therefore, as a consequence, they likely did not engage in service that always offered reflection, collaboration, a shared purpose, or other opportunities to connect service with students' personal values. Hoover and Webster (2004) recommended that faculty conducting service learning activities provide students with greater opportunities to learn about other students and that allow students to move outside of their comfort zones. The authors also recommend that students participating in service learning should receive focused opportunities to reflect upon their role in service learning and that service should not be a "one time event" (Hoover & Webster, 2004, p. 61).…”
Section: Recommendationsmentioning
confidence: 99%
“…National studies have shown that students who engaged in service-learning activities (a) increased their cognitive and social skills (Billig & Klute, 2003;Klute & Billig, 2002), (b) developed a more positive attitude toward school (Furco, 2002;Hecht, 2002), (c) made connections to their community and cultural heritage (Billig & Meyer, 2002;Billig, Meyer, & Hofschire, 2003), and (d) increased their civic engagement knowledge and awareness of societal issues (Furco, 2002;Melchior & Bailis, 2002) in comparison to counterparts who did not participate in service-learning activities. Other benefits associated with service-learning activities include improvements in students' moral reasoning and problem solving (Conrad & Hedin, 1982, 1991Eyler, Root, & Giles, 1998), growth in personal development (Giles & Eyler, 1994Yates & Youniss, 1996), more respectful attitudes toward diverse groups (Hoover & Webster, 2004;Yates & Youniss, 1996), an enhanced ability to connect academic learning to societal issues and concerns (Eyler, Giles, Stenson, & Gray, 2000), and a practical understanding of theories (Eyler et al, 2000). Matthews and Menna (2003) suggested that community-based learning opportunities provide a way to increase the engagement of problem students, and Hoffman and Xu (2002) found that community service was negatively related to delinquency but only in low-minority schools.…”
Section: Benefits Of Servicementioning
confidence: 99%